Effect of age and waste crumb rubber aggregate proportions on flexural characteristics of self‐compacting rubberized concrete. (17th March 2021) - Wanasinghe, Dimuthu; Aslani, Farhad; Dai, Kunyou
Abstract: Generation of waste has been a significant problem in recent decades in many engineering fields. Self‐compacting rubberized concrete (SCRC) is a new type of SCC, which replaces part of natural aggregates by rubber aggregates in SCC to increase the application range of waste tyre rubber. This study investigates the effect of age and crumb rubber aggregate ratio on fresh and mechanical performance. Eight different SCRC mixtures using 2–5 mm rubber aggregates to replace 10%, 20%, 30%, and 40% natural aggregates by volume respectively, and 5–10 mm rubber aggregates to replace 10%, 20%, 30%, and 40% natural aggregates by volume respectively, are tested after 7, 28, 56, and 91 days for their mechanical properties. Results show that both the compressive and the tensile strength increase with the aging time, both of these properties drop with the amount and size of the crumb rubber content. Similar to compressive and tensile properties, flexural toughness and the modulus of rupture showed increased with the aging time. Small addition of crumb rubber has shown improvements in both rupture and fracture toughness properties, which diminishes when the crumb rubber content becomes significantly large.